Extended vocal repertoire of the bromeligenous treefrog Scinax belloni (Anura:Hylidae) - Bang, Davi Lee; Vidigal, Izadora; Marinho, Pedro [UNESP]; Giaretta, Ariovaldo Antonio (Taylor & Francis Ltd, 2022)
Scinax belloni is a small bromeligenous treefrog that lives in the mountainous areas of southeastern Brazil. The call of the species has been previously described, but recently gathered data revealed an unreported acoustic unit that we describe herein. Intraspecific variation within the species call was also updated based on an increased sample size. The call is composed of two types of multipulsed notes: a short note, which is in agreement with the previous description, and a trill note that is emitted in association with the short note. The trill note was likely not reported in the previous description because of the small sample size. Further studies should elucidate the social function of the trill note. Acoustic units somewhat resembling the trill note are shared by a few other Scinax species, but the nomenclatural instability of these calls hamper detailed comparisons. This highlights the need for a standardized and comparative acoustic analysis to elucidate homologous and comparable acoustic units among the bromeligenous Scinax species.
Keywords: Atlantic forest; Bioacoustics; Mantiqueira mountain range; Scinaxinae